The Effectiveness of Traditional Game Therapy in Improving Social Skills in Elementary School Students 060952 Medan Labuhan District - Johannes, Johannes; Fitriani, Enny; Muhammadi, Muhammadi (PT Inovasi Pratama Internasional, 2024)
Social skills are very important for the development of elementary school children. Traditional play therapy offers an alternative method for education that has the potential to improve social skills through group interactions and real-life experiences. This is different from the conventional approach which often centers on academic aspects. The aim of this study was to evaluate how effective traditional play therapy is in improving the social skills of children in elementary school and compare it with more conventional methods. This is the experimental design used for this study with a control group. Children in elementary school are divided into two groups. The experimental group received traditional play therapy, while the control group carried out routine activities. Data was collected through teacher observations, assessments, and social skills questionnaires before and after six weeks of intervention. The results of the analysis showed that, compared with the control group, the experimental group showed significant improvements in social skills. Communication, cooperation and conflict resolution show improvement. These results indicate that traditional play therapy is effective in improving the social skills of elementary school children. According to this research, traditional play therapy can be included in the school curriculum as a tool to improve social skills in a comprehensive and enjoyable way.